Történelemtankönyvek a budapesti fiú-középiskolákban Klebelsberg Kuno minisztersége idején - Albert B., Gábor (Magyar Pedagógia, 2017)
This study adds to the recent body of research on textbook usage in Hungarian schools (Gunčaga and Tóth, 2013; Molnár-Kovács, 2015) with a primary focus on textbook usage and school history in the era in which Kuno Klebelsberg served as minister of religion and public education (1922–1931) (Albert, 2012, 2013a, 2013b). The article analyses factors that influenced textbook usage and selection in all-boys schools in Budapest in that period. Earlier studies on the history of textbooks (Unger, 1976) and the history of textbook approval (Szebenyi, 1994) cover the shrinking textbook market in the Klebelsberg period compared to that of the Austro-Hungarian Empire (1867–1918), a decrease which was intensified by religious segregation. In contrast with earlier scholarship (Unger, 1976; Szebenyi, 1994), this study demonstrates that a fairly open and pluralistic textbook market formed in Hungary in the period under review, especially in Budapest, after the Treaty of Trianon (1920) between Hungary and the Allies of World War I. Religious segregation was not deepened; quite the contrary, publishers and schools saw greater opportunities in textbook distribution and selection.